2023
DOI: 10.1002/1873-3468.14602
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the motor domain of centromere‐associated protein E in complex with a non‐hydrolysable ATP analogue

Abstract: Centromere-associated protein E (CENP-E) is a kinesin motor protein essential for mitosis and a new target for anticancer agents with less side effects. To rationally design anticancer drug candidates based on structure, it is important to determine the three-dimensional structure of the CENP-E motor domain bound to its inhibitor. Here, we report the first crystal structure of the CENP-E motor domain in complex with a non-hydrolysable ATP analogue, adenylyl-imidodiphosphate (AMPPNP). Furthermore, the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent study has revealed the crystal structure of CENP-E motor domain in complex with AMPPNP. And the helix α4 is required for the slow binding of CENP-E to microtubules (Shibuya et al, 2023). In the future, crystal structures of CENP-E in complex with specific inhibitors will help to elucidate the mechanisms of kinesin motors and the development of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has revealed the crystal structure of CENP-E motor domain in complex with AMPPNP. And the helix α4 is required for the slow binding of CENP-E to microtubules (Shibuya et al, 2023). In the future, crystal structures of CENP-E in complex with specific inhibitors will help to elucidate the mechanisms of kinesin motors and the development of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%